ANALISIS BIAYA PRODUKSI DAN TITIK IMPAS USAHA KECIL PEMBUATAN SARI JAHE INSTAN - Makmur (Jurnal Ilmiah Cano Ekonomos, 2017)
This research aims to detect cost of goods manufactured and break even point sari jahe instan Rokan Hulu Regency. performed on december 2014 until with may 2015. This research intent to know cost structure, cost of goods manufacture, income, and break even point efficiency of sari jahe instan. This research constitute case study on Sari Jahe Instan Zahra belongs to Sumartini's in Rambah Utama village, district Rambah Samo, Rokan Hulu Regency. with respondent as source of observational data information is effort owner that at a swoop manager and employ as much 3 person. Result observationaling to point out that Cost structure consisting of Fixed Cost as big as Rp 108.300,- and variable cost as big as Rp 2.082.000,- Full scale production cost as big as Rp 2.190. 300,- Effort acceptance as big as Rp 2.880.000,- its outgrows propertied be Rp 689.700,- with point r/c ratio as big as 1,31 meanwhile total BEP productions as much 274 boxs and BEP assesses Rp 6.084,-/box.